A scoping study of â€œSnapshotâ€ teaching framework - Gina Selvira Yanti; Rafika Nurhidayah (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2022)
Despite the emergence of Dogme ELT in the 2000s, only small numbers of academic research employing this approach were documented, especially in the context of teaching English Speaking skills in Indonesian higher education. Also, as a response to Indonesian studentsâ€™ unsatisfied performance in English skills, this study was aimed to introduce and propose an instructional framework using